Aza‐ and Mixed Thia/Aza‐Macrocyclic Receptors with Quinoline‐Bearing Pendant Arms for Optical Discrimination of Zinc(II) or Cadmium(II) Ions. Issue 8 (18th August 2020) - Garau, Alessandra; Aragoni, M. Carla; Arca, Massimiliano; Bencini, Andrea; Blake, Alexander J.; Caltagirone, Claudia; Giorgi, Claudia; Lippolis, Vito; Scorciapino, Mariano Andrea
Abstract: The synthesis and coordination properties of two fluorescent chemosensors, featuring [9]aneN3 (1, 4, 7‐triazacyclononane; L1 ) and [12]aneNS3 (1‐aza‐4, 7, 10‐trithiacyclododecane; L2 ) as receptor units, and a quinoline pendant arm with an amide group as a functional group spacer are described. The optical responses of L1 and L2 in the presence of several metal ions were analysed in MeCN/H2 O (1 : 4 v/v) solutions. A selective chelation enhancement of fluorescence (CHEF) effect was observed in the presence of Zn 2+ in the case of L1, and in the presence of Cd 2+ in the case of L2, following the formation of a 1 : 1 and a 1 : 2 metal/ligand complex, respectively, which was also confirmed by potentiometric measurements. 1 H and 13 C NMR measurements in CD3 CN/CDCl3 in combination with molecular mechanics calculations show that for both complexes of L1 and L2 with Zn 2+ and Cd 2+, respectively, the coordination of the carbonyl group from the pendant arm could be the origin of the observed optical selectivity. Abstract : A strong arm : The sensing and recognition properties of two fluorescent chemosensors featuring [9]aneN3 (L1 ) and [12]aneNS3 (L2 ) as receptor units and a quinoline pendant arm with an amide group as functional group spacer have been studied. The combination of these units resulted in a selective optical response of L1 and L2 through a CHEF effect towards Zn 2+ and Cd 2+, following the formation of a 1 : 1 and a 1 : 2 metal‐to‐ligand complex, respectively.